Complement and T cells - Kemper, Claudia (Henry Stewart Talks, 2017)
Complement in the regulation of general immune cell activity, Indirect (APC-mediated) effects of complement on T cell activation, Direct effects of complement on T cell responses, Role of autocrine and intracellular complement (the Complosome) in Th1 responses, Crosstalk between the NLRP3 inflammasome and the Complosome, Regulation of cell metabolism by intracellular/autocrine complement